2004
DOI: 10.1108/01437730410512787
|View full text |Cite
|
Sign up to set email alerts
|

Leading the diverse workforce

Abstract: US demographers predict that women, people of color and ethnic minorities will represent over 50 percent of all new entrants to the US workforce by 2008. This shift in demographics plus the pressure from a growing competitive global marketplace are forcing organizations to rethink models of business success. The authors describe how organizations can ensure their readiness to effectively align business strategies with today's demographic and market realities to achieve growth, profitability, and sustainability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…While a gender-diverse teaching workforce is typically discussed in educational literature in terms of benefits for students, gender diversity is a goal in numerous industries internationally. Workforce diversity (of age, gender, ethnicity, and religion) is frequently pursued to foster an inclusive workplace and to ensure that an organization is reflective of the broader community it serves (McCuiston, Ross Wooldridge, & Pierce, 2004). Notably, such efforts have been found to positively impact employees' job satisfaction and performance (Pitts, 2009).…”
Section: The Organizational Level: Workforce Gender Diversitymentioning
confidence: 99%
“…While a gender-diverse teaching workforce is typically discussed in educational literature in terms of benefits for students, gender diversity is a goal in numerous industries internationally. Workforce diversity (of age, gender, ethnicity, and religion) is frequently pursued to foster an inclusive workplace and to ensure that an organization is reflective of the broader community it serves (McCuiston, Ross Wooldridge, & Pierce, 2004). Notably, such efforts have been found to positively impact employees' job satisfaction and performance (Pitts, 2009).…”
Section: The Organizational Level: Workforce Gender Diversitymentioning
confidence: 99%
“…The same study showed that heterogeneity in functional background and race/ethnicity may improve group performance through the contribution of diverse information and skills. McCuiston et al (2004) argued that diversity can improve companies' bottom line by improving corporate culture, improving relationships with clients, retaining talented employees, decreasing complaints, and improving employee morale. Although the creation of cultural "enclaves" within organisations can provide the space where cultural, minority, groups find social support and networking it is seen to weaken links and cohesion with other cultural groups (Loosemore et al 2010).…”
Section: Management Of Culturally Diversified Project Teamsmentioning
confidence: 99%
“…Drawing largely upon research into corporate performance, diverse organisations outperform homogenous ones in a plethora of ways. Diverse organisations are: more productive; better attract and retain talent; foster higher levels of employee satisfaction; and boast higher levels of public legitimacy (Davis et al , 2016; McCuiston et al , 2004).…”
Section: The Global Context: Why Diversity?mentioning
confidence: 99%